Morning Glory Disc Anomaly: Characteristic MR Imaging Findings - Ellika, S.; Robson, C.D.; Heidary, G.; Paldino, M.J. (American Journal of Neuroradiology, 2013)
SUMMARY: Establishing the diagnosis of morning glory disc anomaly is crucial to appropriate patient treatment. Although typically made clinically, the diagnosis is not always straightforward, especially in circumstances where physical examination is limited. The goal of this study was to define the spectrum and frequency of orbital findings in a series of patients with funduscopically-confirmed morning glory disc anomaly by using MR imaging. MR imaging demonstrated 3 findings in all patients: 1) funnel-shaped morphologic pattern of the posterior optic disc with elevation of the adjacent retinal surface; 2) abnormal tissue associated with the distal intraorbital segment of the ipsilateral optic nerve, with effacement of the regional subarachnoid spaces; and 3) discontinuity of the uveoscleral coat. These findings were not observed in any of the unaffected globes of the study patients. In summary, these consistent and characteristic findings of morning glory disc anomaly should allow for accurate differentiation from other ocular anomalies and have the potential to guide appropriate management of this patient population. MGDAmorning glory disc anomaly